A preparation method of dual non-precious metal catalyst material and corresponding materials
By preparing bi-non-precious metal catalyst materials, the combination of polyhedral catalyst precursor with a high specific surface area and carbon nanotubes is used to combine the secondary doping process and the bimetal coordination effect of Cu and Mn, the problems of scarcity, high cost and poor stability of precious metal catalysts are solved, and efficient and economical catalytic performance and long life are achieved.
Patent Information
- Application Number
- CN202410117500.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-01-29
AI Technical Summary
Existing precious metal catalysts have problems of scarcity, high cost and poor stability, which limit their large-scale application in fuel cells.
Using bi-non-noble metal catalyst materials, the polyhedral catalyst precursor with high specific surface area is synthesized, and combined with supported carbon nanotubes, the content of metal elements is increased through the secondary doping process, and the bimetallic coordination effect of Cu and Mn is used to improve the stability of the catalyst.
It reduces the preparation cost of the catalyst, improves the catalytic activity and conductivity, extends the service life of the catalyst, and has good comprehensive performance and development prospects.
Smart Images

Figure CN117954642B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell catalyst materials, and in particular to a preparation method of a dual non-noble metal catalyst material and corresponding materials. Background Art
[0002] With the rapid development of society, the massive consumption of fossil energy has caused serious environmental pollution. It is crucial to find clean, renewable and sustainable energy alternatives. Environmentally friendly fuel cells, as a new electrochemical technology, have attracted great attention from the scientific community. Fuel cell devices are affected by oxygen reduction during application, and various precious metal materials such as gold, palladium and platinum have become the preferred elements to improve oxygen reduction. However, these precious metals have the disadvantages of scarcity, high cost and poor long-term stability, which hinder their large-scale practical application.
[0003] Transition metal compounds are highly valued due to their abundant natural resources, low cost, high oxygen reduction catalytic ability and excellent electrochemical durability. However, single transition metal catalysts have problems such as insufficient active centers, poor stability and metal dissolution. Metal-organic frameworks are a new type of organic framework composed of organic ligands and metal ions. They have a high specific surface area and can anchor active sites, and are used as effective carriers for metal doping.
[0004] Therefore, how to prepare a catalyst with high catalytic activity and good stability while reducing costs has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of this, in order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a dual non-precious metal catalyst material and corresponding materials.
[0006] In one aspect, the present invention provides a method for preparing a dual non-precious metal catalyst material, the method comprising:
[0007] Step 1: Preparation of polyhedral catalyst precursor
[0008] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio to carry out a pre-reaction, a divalent Cu salt and a divalent Mn salt are added to the pre-reaction solution, and the mixture is stirred for reaction, and the solution after the stirring reaction is centrifuged, washed and dried to obtain a reaction product, and the reaction product is subjected to high-temperature sintering in a protective atmosphere to obtain a polyhedral catalyst precursor;
[0009] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0010] Adding a polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt to a mixed solvent of methanol and dimethylformamide according to a ratio and stirring the mixture for reaction, centrifugally washing and drying the solution after the stirring reaction to obtain a reaction product, and subjecting the reaction product to high-temperature sintering in a protective atmosphere to obtain a secondary doped polyhedral catalyst precursor;
[0011] Step 3: Preparation of dual non-precious metal catalyst materials
[0012] The carbon nanotubes are activated, and the secondary doped polyhedral catalyst precursor and the activated carbon nanotubes are added into a loading solvent according to a ratio for ultrasonic composite loading, and the solution after ultrasonic composite loading is centrifugally washed and dried to obtain a dual non-precious metal catalyst material.
[0013] Preferably, in step 1 of the method for preparing the dual non-precious metal catalyst material of the present invention, the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol and dimethylformamide is 1:2-4:50-100:100-200, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt and divalent Mn salt is 1:0.2-0.4:0.2-0.4.
[0014] Preferably, in step one of the preparation method of the dual non-precious metal catalyst material of the present invention, the pre-reaction time is 0.5-1h, the stirring reaction time is 12-24h, the centrifugal washing speed is 3000-4000rmp, the number of centrifugal washing is 4-6 times, the drying temperature is 40-60°C, and the drying time is 6-12h.
[0015] Preferably, in step one of the preparation method of the dual non-precious metal catalyst material of the present invention, the reaction product is subjected to high-temperature sintering treatment in a protective atmosphere to obtain a polyhedral catalyst precursor, including: in a nitrogen or argon atmosphere, the reaction product is heated to 950-1000°C at a heating rate of 2-5°C / min, then sintered for 2-4h, and naturally cooled to obtain a polyhedral catalyst precursor.
[0016] Preferably, in step 2 of the method for preparing the dual non-precious metal catalyst material of the present invention, the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol and dimethylformamide is 1:10-20:10-20:100-150:200-300.
[0017] Preferably, in step 2 of the preparation method of the dual non-precious metal catalyst material of the present invention, the stirring reaction time is 6-12 hours, the rotation speed of the centrifugal washing is 5000-6000 rpm, the number of centrifugal washing is 4-6 times, the drying temperature is 40-60°C, and the drying time is 6-12 hours.
[0018] Preferably, in step 2 of the preparation method of the dual non-precious metal catalyst material of the present invention, the reaction product is subjected to high-temperature sintering treatment in a protective atmosphere to obtain a secondary doped polyhedral catalyst precursor, including: in a nitrogen or argon atmosphere, the reaction product is heated to 850-900°C at a heating rate of 2-5°C / min, then sintered for 1-2h, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor.
[0019] Preferably, in step three of the preparation method of the dual non-precious metal catalyst material of the present invention, the carbon nanotubes are activated, including: adding 1 part by weight of carbon nanotubes and 0.5-1 part by weight of hexadecyltrimethylammonium bromide to an activation treatment solution consisting of 1-5 parts by weight of ethanol and 300-500 parts by weight of deionized water, ultrasonically reacting for 1-2 hours, centrifuging the solution after the ultrasonic reaction at a speed of 4000-5000 rpm for 4-6 times, and drying the product after centrifugal washing at a temperature of 40-60°C for 6-12 hours to obtain the activated carbon nanotubes.
[0020] Preferably, in step three of the preparation method of the dual non-precious metal catalyst material of the present invention, the secondary doped polyhedral catalyst precursor and the activated carbon nanotubes are added to the loading solvent according to the ratio for ultrasonic composite loading, and the solution after ultrasonic composite loading is centrifuged and dried to obtain the dual non-precious metal catalyst material, including: adding 1 weight part of secondary doped polyhedral catalyst precursor and 0.05-0.1 weight part of activated carbon nanotubes to 200-500 weight parts of ethanol for ultrasonic composite loading for 2-4h, centrifugally washing the solution after ultrasonic composite loading at a speed of 4000-5000rmp, and drying the product after centrifugal washing at a temperature of 40-60°C for 6-12h to obtain the dual non-precious metal catalyst material.
[0021] On the other hand, the present invention provides a dual non-precious metal catalyst material, which is prepared according to the above method.
[0022] The preparation method of the dual non-noble metal catalyst material and the corresponding material of the present invention have the following beneficial effects:
[0023] 1. Use non-precious metal elements as raw materials. Compared with precious metals such as gold, palladium and platinum, these non-precious metals are abundant in nature and low in price, and the preparation cost is greatly reduced.
[0024] 2. By synthesizing a polyhedral catalyst precursor with high specific surface area and the ability to anchor transition metal active sites, combined with loaded carbon nanotubes, the catalyst has high catalytic activity and conductivity.
[0025] 3. Through the secondary doping process, the content of metal elements doped in the catalyst is increased and the catalytic performance is improved.
[0026] 4. The use of Cu and Mn, two transition metals that do not undergo Fenton reaction, and the use of bimetallic coordination make the catalyst have better stability and longer service life. It has good comprehensive performance and development prospects and is suitable for application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a scanning electron microscope (SEM) image of a polyhedral catalyst precursor prepared in step 1 of exemplary embodiment 1 of the present invention;
[0029] Figure 2 This is a transmission electron microscope (TEM) image of the polyhedral catalyst precursor prepared in step 1 of exemplary embodiment 2 of the present invention;
[0030] Figure 3 This is an X-ray energy dispersive spectrometer (EDS) surface scanning result diagram of the polyhedral catalyst precursor prepared in step 1 of exemplary embodiment 2 of the present invention;
[0031] Figure 4 Transmission electron microscope (TEM) image of the dual non-noble metal catalyst prepared in exemplary embodiment 3 of the present invention;
[0032] Figure 5 Transmission electron microscope (TEM) image of the dual non-noble metal catalyst prepared in exemplary embodiment 4 of the present invention;
[0033] Figure 6 This is an X-ray energy dispersive spectrometer (EDS) surface scanning result diagram of the dual non-precious metal catalyst prepared in exemplary embodiment 4 of the present invention;
[0034] Figure 7 A cyclic voltammetry (CV) curve diagram of a dual non-noble metal catalyst prepared in exemplary embodiment 5 of the present invention;
[0035] Figure 8 It is a comparison diagram of the linear sweep voltammetry (LSV) curves of the dual non-precious metal catalyst prepared in exemplary embodiment 5 of the present invention and the commercial Pt / C catalyst. DETAILED DESCRIPTION
[0036] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0037] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.
[0038] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0039] Example 1
[0040] Preparation method of dual non-precious metal catalyst material:
[0041] Step 1: Preparation of polyhedral catalyst precursor
[0042] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio for pre-reaction for 0.5 h, divalent Cu salt and divalent Mn salt are added to the pre-reaction solution, and the reaction is stirred for 12 h, wherein the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol, and dimethylformamide is 1:2:50:100, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt, and divalent Mn salt is 1:0.2:0.2, the solution after the stirring reaction is centrifuged and washed 4 times at a speed of 3000 rpm, and the product after centrifugal washing is dried at a temperature of 40°C for 6 h to obtain a reaction product, and the reaction product is heated to 950°C at a heating rate of 2°C / min in a nitrogen atmosphere, sintered for 2 h, and naturally cooled to obtain a polyhedral catalyst precursor;
[0043] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0044] A polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt are added to a mixed solvent of methanol and dimethylformamide according to a ratio, and stirred for reaction for 6 hours, wherein the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol, and dimethylformamide is 1:10:10:100:200, the solution after the stirring reaction is centrifuged and washed 4 times at a speed of 5000 rpm, the product after centrifugal washing is dried at a temperature of 40°C for 6 hours to obtain a reaction product, the reaction product is heated to 850°C at a heating rate of 2°C / min in a nitrogen atmosphere, sintered for 1 hour, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor;
[0045] Step 3: Preparation of dual non-precious metal catalyst materials
[0046] According to the ratio of parts by weight, 1 part by weight of carbon nanotubes and 0.5 parts by weight of hexadecyltrimethylammonium bromide are added to an activation treatment solution consisting of 1 part by weight of ethanol and 300 parts by weight of deionized water, and ultrasonically reacted for 1 hour, and the solution after ultrasonic reaction was centrifuged and washed 4 times at a speed of 4000 rpm, and the product after centrifugal washing was dried at a temperature of 40° C. for 6 hours to obtain activated carbon nanotubes;
[0047] According to the ratio of weight parts, 1 weight part of secondary doped polyhedral catalyst precursor and 0.05 weight part of activated carbon nanotubes were added to 200 weight parts of ethanol for ultrasonic composite loading for 2 hours, the solution after ultrasonic composite loading was centrifuged at a speed of 4000 rpm, and the product after centrifugal washing was dried at 40°C for 6 hours to obtain a dual non-precious metal catalyst material.
[0048] Example 2
[0049] Preparation method of dual non-precious metal catalyst material:
[0050] Step 1: Preparation of polyhedral catalyst precursor
[0051] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio for pre-reaction for 0.6 h, divalent Cu salt and divalent Mn salt are added to the pre-reaction solution, and the reaction is stirred for 16 h, wherein the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol, and dimethylformamide is 1:2.5:60:120, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt, and divalent Mn salt is 1:0.25:0.25, and the solution after the stirring reaction is centrifuged and washed 4 times at a speed of 3200 rpm, and the product after centrifugal washing is dried at a temperature of 45°C for 8 h to obtain a reaction product, and the reaction product is heated to 960°C in a nitrogen atmosphere at a heating rate of 3°C / min, sintered for 2.5 h, and naturally cooled to obtain a polyhedral catalyst precursor;
[0052] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0053] A polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt are added to a mixed solvent of methanol and dimethylformamide according to a ratio, and stirred for reaction for 8 hours, wherein the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol, and dimethylformamide is 1:12:12:110:220, the solution after the stirring reaction is centrifuged and washed 4 times at a speed of 5200 rpm, the product after centrifugal washing is dried at a temperature of 45°C for 8 hours to obtain a reaction product, the reaction product is heated to 860°C at a heating rate of 3°C / min in a nitrogen atmosphere, sintered for 1.2 hours, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor;
[0054] Step 3: Preparation of dual non-precious metal catalyst materials
[0055] According to the ratio of parts by weight, 1 part by weight of carbon nanotubes and 0.6 parts by weight of hexadecyltrimethylammonium bromide were added to an activation treatment solution consisting of 2 parts by weight of ethanol and 350 parts by weight of deionized water, and ultrasonic reaction was performed for 1.2 hours. The solution after ultrasonic reaction was centrifuged and washed 4 times at a speed of 4200 rpm, and the product after centrifugal washing was dried at a temperature of 45°C for 8 hours to obtain activated carbon nanotubes;
[0056] According to the ratio of weight parts, 1 weight part of secondary doped polyhedral catalyst precursor and 0.06 weight part of activated carbon nanotubes were added to 300 weight parts of ethanol and ultrasonically composite loaded for 2.5 hours. The solution after ultrasonic composite loading was centrifuged and washed at a speed of 4200 rpm. The product after centrifugal washing was dried at 45°C for 8 hours to obtain a dual non-precious metal catalyst material.
[0057] Example 3
[0058] Preparation method of dual non-precious metal catalyst material:
[0059] Step 1: Preparation of polyhedral catalyst precursor
[0060] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio for pre-reaction for 0.75 h, divalent Cu salt and divalent Mn salt are added to the pre-reaction solution, and the reaction is stirred for 18 h, wherein the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol, and dimethylformamide is 1:3:75:150, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt, and divalent Mn salt is 1:0.3:0.3, the solution after the stirring reaction is centrifuged and washed 5 times at a speed of 3500 rpm, and the product after centrifugal washing is dried at a temperature of 50°C for 9 h to obtain a reaction product, and the reaction product is heated to 985°C in an argon atmosphere at a heating rate of 3.5°C / min, sintered for 3 h, and naturally cooled to obtain a polyhedral catalyst precursor;
[0061] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0062] A polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt are added to a mixed solvent of methanol and dimethylformamide according to a ratio, and stirred for reaction for 9 hours, wherein the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol, and dimethylformamide is 1:15:15:125:250, the solution after the stirred reaction is centrifuged and washed 5 times at a speed of 5500 rpm, the product after centrifugal washing is dried at a temperature of 50°C for 9 hours to obtain a reaction product, the reaction product is heated to 875°C at a heating rate of 3.5°C / min in an argon atmosphere, sintered for 1.5 hours, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor;
[0063] Step 3: Preparation of dual non-precious metal catalyst materials
[0064] According to the ratio of parts by weight, 1 part by weight of carbon nanotubes and 0.75 parts by weight of hexadecyltrimethylammonium bromide were added to an activation treatment solution consisting of 3 parts by weight of ethanol and 400 parts by weight of deionized water, and ultrasonically reacted for 1.5 hours. The solution after ultrasonic reaction was centrifuged and washed 5 times at a speed of 4500 rpm, and the product after centrifugal washing was dried at a temperature of 50° C. for 9 hours to obtain activated carbon nanotubes;
[0065] According to the ratio of weight parts, 1 weight part of secondary doped polyhedral catalyst precursor and 0.075 weight part of activated carbon nanotubes were added to 350 weight parts of ethanol for ultrasonic composite loading for 3 hours, the solution after ultrasonic composite loading was centrifuged at a speed of 4500 rpm, and the product after centrifugal washing was dried at 50°C for 9 hours to obtain a dual non-precious metal catalyst material.
[0066] Example 4
[0067] Preparation method of dual non-precious metal catalyst material:
[0068] Step 1: Preparation of polyhedral catalyst precursor
[0069] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio for pre-reaction for 0.9 h, divalent Cu salt and divalent Mn salt are added to the pre-reaction solution, and stirred for reaction for 20 h, wherein the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol, and dimethylformamide is 1:3.5:90:180, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt, and divalent Mn salt is 1:0.35:0.35, and the solution after stirring reaction is centrifuged and washed 6 times at a speed of 3800 rpm, and the product after centrifugal washing is dried at a temperature of 55°C for 10 h to obtain a reaction product, and the reaction product is heated to 990°C in an argon atmosphere at a heating rate of 4°C / min, sintered for 3.5 h, and naturally cooled to obtain a polyhedral catalyst precursor;
[0070] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0071] A polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt are added to a mixed solvent of methanol and dimethylformamide according to a ratio, and the mixture is stirred and reacted for 10 hours, wherein the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol, and dimethylformamide is 1:18:18:140:280, the solution after the stirring reaction is centrifuged and washed 6 times at a speed of 5800 rpm, the product after centrifugal washing is dried at a temperature of 55°C for 10 hours to obtain a reaction product, the reaction product is heated to 890°C at a heating rate of 4°C / min in an argon atmosphere, and then sintered for 1.8 hours, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor;
[0072] Step 3: Preparation of dual non-precious metal catalyst materials
[0073] According to the ratio of parts by weight, 1 part by weight of carbon nanotubes and 0.9 parts by weight of hexadecyltrimethylammonium bromide were added to an activation treatment solution consisting of 4 parts by weight of ethanol and 450 parts by weight of deionized water, and ultrasonic reaction was performed for 1.8 hours. The solution after ultrasonic reaction was centrifuged and washed 6 times at a speed of 4800 rpm, and the product after centrifugal washing was dried at a temperature of 55° C. for 10 hours to obtain activated carbon nanotubes;
[0074] According to the ratio of weight parts, 1 weight part of secondary doped polyhedral catalyst precursor and 0.08 weight part of activated carbon nanotubes were added to 400 weight parts of ethanol for ultrasonic composite loading for 3.5 hours. The solution after ultrasonic composite loading was centrifuged and washed at a speed of 4800 rpm. The product after centrifugal washing was dried at 55°C for 10 hours to obtain a dual non-precious metal catalyst material.
[0075] Example 5
[0076] Preparation method of dual non-precious metal catalyst material:
[0077] Step 1: Preparation of polyhedral catalyst precursor
[0078] Zinc nitrate hexahydrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio for pre-reaction for 1 hour, divalent Cu salt and divalent Mn salt are added to the pre-reaction solution, and stirred for reaction for 24 hours, wherein the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol, and dimethylformamide is 1:4:100:200, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt, and divalent Mn salt is 1:0.4:0.4, and the solution after stirring reaction is centrifuged and washed 6 times at a speed of 4000 rpm, and the product after centrifugal washing is dried at a temperature of 60°C for 12 hours to obtain a reaction product, and the reaction product is heated to 1000°C at a heating rate of 5°C / min in an argon atmosphere, sintered for 4 hours, and naturally cooled to obtain a polyhedral catalyst precursor;
[0079] Step 2: Preparation of secondary doped polyhedral catalyst precursor
[0080] A polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt are added to a mixed solvent of methanol and dimethylformamide according to a ratio, and the mixture is stirred and reacted for 12 hours, wherein the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol, and dimethylformamide is 1:20:20:150:300, the solution after the stirring reaction is centrifuged and washed 6 times at a speed of 6000 rpm, the product after centrifugal washing is dried at a temperature of 60°C for 12 hours to obtain a reaction product, the reaction product is heated to 900°C at a heating rate of 5°C / min in an argon atmosphere, and then sintered for 2 hours, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor;
[0081] Step 3: Preparation of dual non-precious metal catalyst materials
[0082] According to the ratio of parts by weight, 1 part by weight of carbon nanotubes and 1 part by weight of hexadecyltrimethylammonium bromide are added to an activation treatment solution consisting of 5 parts by weight of ethanol and 500 parts by weight of deionized water, and ultrasonically reacted for 2 hours, and the solution after ultrasonic reaction was centrifuged and washed 6 times at a speed of 5000 rpm, and the product after centrifugal washing was dried at a temperature of 60° C. for 12 hours to obtain activated carbon nanotubes;
[0083] According to the ratio of weight parts, 1 weight part of secondary doped polyhedral catalyst precursor and 0.1 weight part of activated carbon nanotubes were added to 500 weight parts of ethanol for ultrasonic composite loading for 4 hours, the solution after ultrasonic composite loading was centrifuged at a speed of 5000 rpm, and the product after centrifugal washing was dried at 60°C for 12 hours to obtain a dual non-precious metal catalyst material.
[0084] Example 6
[0085] Hitachi SU8020 cold field emission scanning electron microscope was used to characterize the microscopic morphology of the polyhedral catalyst precursor prepared in step 1 of Example 1. 0.5 mg of the polyhedral catalyst precursor was placed in 10 ml of ethanol and ultrasonicated for 1 h. The upper turbid liquid was placed on a polished silicon wafer and dried at 40°C for 0.2 h before testing. The results are shown in Figure 1 .
[0086] The microscopic morphology of the polyhedral catalyst precursor prepared in step 1 of Example 2 was characterized using a Talos F200X G2 transmission electron microscope. Figure 2 ; and perform spectrum analysis on it, the results are shown in Figure 3 The microscopic morphology of the dual non-precious metal catalyst prepared in Example 3 was characterized, and the results are shown in Figure 4 The microscopic morphology of the dual non-precious metal catalyst prepared in Example 4 was characterized, and the results are shown in Figure 5 ; and perform spectrum analysis on it, the results are shown in Figure 6 The test process includes: placing 0.2 mg of polyhedral catalyst precursor or dual non-precious metal catalyst in 10 ml of ethanol and ultrasonicating for 1 hour, taking the upper turbid liquid and dropping it on the grid, and testing it after natural drying.
[0087] Cyclic voltammetry (CV) curve test of the dual non-precious metal catalyst prepared in Example 5 was performed using an Autolab electrochemical workstation in a three-electrode system. The results are shown in Figure 7 . Cyclic voltammetry curve test was carried out on an electrochemical workstation (PGSA302) using a three-electrode system, with glassy carbon as the working electrode, saturated calomel as the reference electrode, platinum wire as the counter electrode, and a rotating disk electrode as the substrate of the working electrode. 5 mg of dual non-precious metal catalyst material (hereinafter referred to as CuMn-NC@CNT), 50 μL of 20 wt% Nafion solution, and 450 μL of isopropanol were added to 500 μL of deionized water and ultrasonicated for 1 h to obtain electrode catalyst ink, and 18 μL of the ink was coated on the working electrode, and then tested in an O2-saturated 0.1 mol / L KOH solution.
[0088] The linear sweep voltammetry (LSV) curves of the dual non-precious metal catalyst prepared in Example 5 and the commercial Pt / C catalyst were tested using an Autolab electrochemical workstation in a three-electrode system. The results are shown in Figure 8 . Linear sweep voltammetry curve test was carried out on an electrochemical workstation (PGSA302) using a three-electrode system, with glassy carbon as the working electrode, saturated calomel as the reference electrode, platinum wire as the counter electrode, and a rotating disk electrode as the substrate of the working electrode. 5 mg CuMn-NC@CNT or Pt / C catalyst, 50 μL 20 wt% Nafion solution and 450 μL isopropanol were added to 500 μL deionized water and ultrasonicated for 1 h to obtain electrode catalyst ink, and 18 μL of the ink was coated on the working electrode, and then tested in an O2-saturated 0.1 mol / L KOH solution.
[0089] like Figure 1 As shown, the scanning electron microscope (SEM) image of the polyhedral catalyst precursor prepared according to step 1 of Example 1 shows that the catalyst precursor is a regular polyhedral structure, similar to the structural framework of ZIF, which can carry more Cu-Nx and Mn-Nx active groups, which is conducive to efficient catalytic activity.
[0090] Figure 2 This is a transmission electron microscope (TEM) image of the polyhedral catalyst precursor prepared in step 1 of exemplary embodiment 2 of the present invention; Figure 3 This is an X-ray energy dispersive spectrometer (EDS) surface scanning result diagram of the polyhedral catalyst precursor prepared in step 1 of exemplary embodiment 2 of the present invention, wherein: Figure 3 (a), (b), (c) and (d) in the figure represent the surface scanning results of Cu, Mn, N and C elements respectively; Figure 2 and Figure 3 As shown, the polyhedral catalyst is composed of Cu, Mn, N, and C elements, and the Cu and Mn elements are evenly distributed on the polyhedral structure, which makes the catalytic active sites evenly dispersed and the catalytic performance higher.
[0091] Figure 4 Transmission electron microscope (TEM) image of the dual non-precious metal catalyst prepared in exemplary embodiment 3 of the present invention; Figure 4 As shown, the transmission electron microscope (TEM) image of the dual non-precious metal catalyst prepared according to Example 3 shows that the polyhedral catalyst is well loaded on the carbon nanotubes, which is beneficial to improving the conductivity of the catalyst.
[0092] Figure 5 Transmission electron microscope (TEM) image of the dual non-noble metal catalyst prepared in exemplary embodiment 4 of the present invention; Figure 6This is an X-ray energy dispersive spectrometer (EDS) surface scanning result diagram of the dual non-precious metal catalyst prepared in exemplary embodiment 4 of the present invention, wherein: Figure 6 (a), (b), (c) and (d) in the figure represent the surface scanning results of Cu, Mn, N and C elements respectively; Figure 5 and Figure 6 As shown, the carbon nanotubes are composed of C elements, the polyhedral catalysts are composed of Cu, Mn, N, and C elements, and the polyhedral catalysts are better loaded on the carbon nanotubes.
[0093] like Figure 7 As shown, the cyclic voltammetry (CV) curve of the dual non-precious metal catalyst prepared according to Example 5 shows that there is an obvious oxygen reduction peak at around 0.85V, which has good oxygen reduction ability.
[0094] like Figure 8 As shown in the comparison of the linear sweep voltammetry (LSV) curves of the dual non-precious metal catalyst prepared in Example 5 and the commercial Pt / C catalyst, it can be seen that the half-wave potential of the dual non-precious metal catalyst material (hereinafter referred to as CuMn-NC@CNT) is 0.850V and the limiting current density is 6.1mAcm -2 , while the half-wave potential of Pt / C is only 0.830V and the limiting current is only 4.8mAcm -2 , CuMn-NC@CNT has better oxygen reduction activity; after 10,000 cycles of durability cycle test, the half-wave potential of CuMn-NC@CNT only decayed by 7mV, while the half-wave potential of Pt / C decayed by 27mV. CuMn-NC@CNT has better stability and longer service life.
[0095] The preparation method of the dual non-noble metal catalyst material and the corresponding material of the present invention have the following beneficial effects:
[0096] 1. Use non-precious metal elements as raw materials. Compared with precious metals such as gold, palladium and platinum, these non-precious metals are abundant in nature and low in price, and the preparation cost is greatly reduced.
[0097] 2. By synthesizing a polyhedral catalyst precursor with high specific surface area and the ability to anchor transition metal active sites, combined with loaded carbon nanotubes, the catalyst has high catalytic activity and conductivity.
[0098] 3. Through the secondary doping process, the content of metal elements doped in the catalyst is increased and the catalytic performance is improved.
[0099] 4. The use of Cu and Mn, two transition metals that do not undergo Fenton reaction, and the use of bimetallic coordination make the catalyst have better stability and longer service life. It has good comprehensive performance and development prospects and is suitable for application and promotion.
[0100] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a dual non-precious metal catalyst material, characterized in that: The method comprises: Step 1: Preparation of polyhedral catalyst precursor Hexahydrate zinc nitrate and 2-methylimidazole are added to a mixed solvent of methanol and dimethylformamide according to a ratio to carry out a pre-reaction, a divalent Cu salt and a divalent Mn salt are added to the pre-reaction solution, and the solution after the stirring reaction is centrifuged, washed and dried to obtain a reaction product, and the reaction product is subjected to high-temperature sintering in a protective atmosphere to obtain a polyhedral catalyst precursor; Step 2: Preparation of secondary doped polyhedral catalyst precursor Adding a polyhedral catalyst precursor, a divalent Cu salt, and a divalent Mn salt to a mixed solvent of methanol and dimethylformamide according to a ratio and stirring the mixture for reaction, centrifugally washing and drying the solution after the stirring reaction to obtain a reaction product, and subjecting the reaction product to high-temperature sintering in a protective atmosphere to obtain a secondary doped polyhedral catalyst precursor; Step 3: Preparation of dual non-precious metal catalyst materials The carbon nanotubes are activated, and the secondary doped polyhedral catalyst precursor and the activated carbon nanotubes are added into a loading solvent according to a ratio for ultrasonic composite loading, and the solution after ultrasonic composite loading is centrifugally washed and dried to obtain a dual non-precious metal catalyst material.
2. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step 1, the molar ratio of zinc nitrate hexahydrate, 2-methylimidazole, methanol and dimethylformamide is 1:2-4:50-100:100-200, and the molar ratio of zinc nitrate hexahydrate, divalent Cu salt and divalent Mn salt is 1:0.2-0.4:0.2-0.
4.
3. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step 1, the pre-reaction time is 0.5-1h, the stirring reaction time is 12-24h, the speed of centrifugal washing is 3000-4000rmp, the number of centrifugal washing is 4-6 times, the drying temperature is 40-60°C, and the drying time is 6-12h.
4. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step one, the reaction product is subjected to high-temperature sintering treatment in a protective atmosphere to obtain a polyhedral catalyst precursor, including: in a nitrogen or argon atmosphere, heating the reaction product to 950-1000°C at a heating rate of 2-5°C / min, sintering for 2-4h, and naturally cooling to obtain a polyhedral catalyst precursor.
5. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step 2, the molar ratio of the polyhedral catalyst precursor, the divalent Cu salt, the divalent Mn salt, methanol and dimethylformamide is 1:10-20:10-20:100-150:200-300.
6. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step 2, the stirring reaction time is 6-12 hours, the rotation speed of the centrifugal washing is 5000-6000 rpm, the number of centrifugal washing is 4-6 times, the temperature of the drying treatment is 40-60° C., and the drying treatment time is 6-12 hours.
7. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step 2, the reaction product is subjected to high-temperature sintering treatment in a protective atmosphere to obtain a secondary doped polyhedral catalyst precursor, including: in a nitrogen or argon atmosphere, the reaction product is heated to 850-900°C at a heating rate of 2-5°C / min, sintered for 1-2h, and naturally cooled to obtain a secondary doped polyhedral catalyst precursor.
8. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step three, the carbon nanotubes are activated, including: adding 1 part by weight of carbon nanotubes and 0.5-1 part by weight of hexadecyltrimethylammonium bromide to an activation solution consisting of 1-5 parts by weight of ethanol and 300-500 parts by weight of deionized water, ultrasonically reacting for 1-2 hours, centrifuging the solution after the ultrasonic reaction at a speed of 4000-5000 rpm for 4-6 times, and drying the product after centrifugal washing at a temperature of 40-60°C for 6-12 hours to obtain the activated carbon nanotubes.
9. The method for preparing a dual non-noble metal catalyst material according to claim 1, characterized in that: In step three, the secondary doped polyhedral catalyst precursor and the activated carbon nanotubes are added to the loading solvent according to the ratio for ultrasonic composite loading, and the solution after ultrasonic composite loading is centrifuged and dried to obtain a dual non-precious metal catalyst material, including: adding 1 weight part of secondary doped polyhedral catalyst precursor and 0.05-0.1 weight part of activated carbon nanotubes to 200-500 weight parts of ethanol in a weight ratio for ultrasonic composite loading for 2-4 hours, centrifugally washing the solution after ultrasonic composite loading at a speed of 4000-5000rmp, and drying the product after centrifugal washing at a temperature of 40-60°C for 6-12 hours to obtain a dual non-precious metal catalyst material.
10. A dual non-precious metal catalyst material, characterized in that: The dual non-precious metal catalyst material is prepared according to any one of the methods described in claims 1-9.
Citation Information
Patent Citations
Preparation method of high-load Mn-N active site doped carbon material catalyst and application of high-load Mn-N active site doped carbon material catalyst in lithium-sulfur battery
CN113649043A
Preparation method of bimetallic nitrogen-containing porous carbon catalyst
CN115020722A